Glissement du domaine autochtone (Fort George 1840) - Désy, Pierrette (Anthropologica, 2020)
The human habitat in the boreal forest shares common characteristics with the environment and is marked by an intimate relationship between humans and non-humans. However, this is not strictly the case for inhabited space, which provides the ground for rules integrated within a defined social framework. When the Hudson’s Bay Company tried to exile Cree hunters to Ungava in order to trap them there through falsely describing the area as a land of plenty, it was in fact asking them to exploit unfamiliar regions. This request was an attempt at destabilization since, in the symbolic universe of the Cree, each territory was the centre of the world: One “appropriated” a territory by creating it anew, that is, by consecrating it. Clearly, the project of the Company had a fundamental flaw. It was short-lived because in reality it shook the very foundations of territorial belonging among Cree families. Although this attempt at deterritorialisation was an epiphenomenon, it indicates that the Cree had a scientific view of their environment that could not be undermined by commercial ambitions.